2023
DOI: 10.1002/ptr.7791
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spirulina intake on clinical and metabolic parameters in Alzheimer's disease: A randomized, double‐blind, controlled trial

Abstract: The current study aimed to determine the effects of spirulina intake on cognitive function and metabolic status among patients with Alzheimer's disease (AD). This randomized, double-blind, controlled clinical trial was done among 60 subjects with AD. Patients were randomly assigned to receive either 500 mg/day spirulina or a placebo (each n = 30) twice a day for 12 weeks. Mini-mental state examination score (MMSE) was recorded in all patients before and after intervention. Blood samples were obtained at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…In the final section, our study demonstrates how the increased resistance of cultured cells to heavy metal toxicity may be an indication of the potential in vivo protective role of Spirulina, especially for neurological tissues, and should be an inspiration for further research aiming to achieving practical relevance [11].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the final section, our study demonstrates how the increased resistance of cultured cells to heavy metal toxicity may be an indication of the potential in vivo protective role of Spirulina, especially for neurological tissues, and should be an inspiration for further research aiming to achieving practical relevance [11].…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have successfully demonstrated that Spirulina not only has beneficial effects on the development of the nervous system, but it also has a crucial role in the prevention of oxidative stress [8,9], in the treatment of ROS-induced pathologies, and in the development of new treatments for neurodegenerative diseases such as Alzheimer's or Parkinson's [10]. Omid Reza et al, in a randomized, double-blind, controlled trial, demonstrated that the in vivo administration of Spirulina is useful for improving brain function and metabolic pathways in Alzheimer's Disease [11]. Furthermore, it is a rich source of C-Phycocyanin (PCB), an inhibitor of NADPH oxidase that contributes to oxidative stress in various neurological/neurodegenerative diseases [12].…”
Section: Of 13mentioning
confidence: 99%
“…It reduces inflammation by inhibiting the production of pro-inflammatory cytokines; 5 iii) immune system booster: Spirulina has been shown to improve immune function by increasing the production of antibodies and white blood cells; iv) immunomodulatory activity: Spirulina enhances the immune system by increasing the production of antibodies, cytokines, and natural killer cells; v) anticancer activity: Spirulina has been found to have anticancer properties due to its ability to inhibit tumor growth and encourage apoptosis (programmed cell death) in cancer cells; vi) neuroprotective activity: Spirulina protects neurons from oxidative stress and inflammation, which are connected to neurodegenerative illnesses like Parkinson's and Alzheimer's; vii) antidiabetic: Spirulina has been shown to reduce blood sugar levels in animal studies by enhancing insulin sensitivity; viii) cardiovascular health: Spirulina may help lower blood pressure and reduce cholesterol levels, which can improve cardiovascular health; ix) neuroprotective: some studies suggest that Spirulina may have neuroprotective properties due to its ability to reduce inflammation and oxidative stress in the brain. [18][19][20][21] Spirulina is utilized as a dietary supplement for weight loss, diabetes management, cardiovascular health, and skin health. It is used for several purposes including the following: i) nutritional supplement, Spirulina is a valuable origin of vitamins, protein, and minerals.…”
Section: Uses and Pharmacological Activitiesmentioning
confidence: 99%
“…Supplementation considerably improved the Mini-Mental State Examination score, indicating an enhancement in cognitive function. It also had a favorable impact on the metabolic status by lowering C-reactive protein, fasting glucose, insulin levels, and insulin resistance while increasing insulin sensitivity [89].…”
Section: Galizzi Et Al (2023)mentioning
confidence: 99%